[Potteen Making] - Hall, S. C., Mrs., 1800-1881 (1840)
Group of men making pteen in a cottage.
Attributed to unidentified artist.
Catalogue of Irish Topographical Prints and Original Drawings / Rosalind M. Elmes ; New edition revised and enlarged by Michael Hewson - Dublin : Malton Press, 1975
Ireland: its scenery, character, &c / Mr. & Mrs. S. C. Hall - London: How and Parsons, 1841-43.
Keywords: Stills (Distilleries) -- Ireland -- 1830-1840; Pencil drawings -- Irish -- 1830-1840.